2023
DOI: 10.3390/nu15020352
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Patients for Cosmetic Surgery and Aesthetic Procedures: Ensuring an Optimal Nutritional Status for Successful Results

Abstract: Aesthetic and cosmetic medical practices have attracted considerable consumer attention globally. However, possible complications vary and range from mild, self-resolving ecchymoses or edema to more persistent complications. The aim of this review is to identify the nutritional deficits or excesses associated with the major complications of reconstructive surgery, aesthetic surgery, and mini-invasive aesthetic procedures. An additional goal is to provide a bundle of actions for professionals working in the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…14,15 The state of nutrition can significantly impact wound healing and tissue repair after surgical procedures. 16 It has been shown that up to 25% of outpatient plastic surgery patients are at risk of malnutrition. 16,17 Therefore, nutrition can also affect the occurrence of granulomas.…”
Section: Patient's Nutritional Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 The state of nutrition can significantly impact wound healing and tissue repair after surgical procedures. 16 It has been shown that up to 25% of outpatient plastic surgery patients are at risk of malnutrition. 16,17 Therefore, nutrition can also affect the occurrence of granulomas.…”
Section: Patient's Nutritional Statusmentioning
confidence: 99%
“…16 It has been shown that up to 25% of outpatient plastic surgery patients are at risk of malnutrition. 16,17 Therefore, nutrition can also affect the occurrence of granulomas. Malnutrition alters immune response by reducing T cell response, 18 impairs phagocytic function, and alters cytokine and antibody production.…”
Section: Patient's Nutritional Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic surgery contributes to the healing spectrum by offering techniques for functional and aesthetic restoration of tissues. (14) Plastic surgeons specialize in reconstructive and regenerative interventions that can promote wound healing, restore tissue integrity, and improve quality of life. Surgical techniques such as skin grafting, flap surgery, and microvascular anastomosis can be used to close wounds, restore blood supply, and achieve functional and cosmetic outcomes.…”
Section: Contributions Of Plastic Surgerymentioning
confidence: 99%
“…Keloids are more often witnessed in females between the age of 10 and 30 years and tend to resolve during menopause. 22 Thus, pregnancy is considered as an exacerbating factor of keloids and correspondingly, 23 sex hormones, particularly increased oestrogen is thought to act as a physiological risk factor for keloidogenesis. 24 This hormonal contribution has been also indicated by the effect of tamoxifen treatment, which suppressed oestrogen‐induced growth of keloids.…”
Section: Introductionmentioning
confidence: 99%